PENGGUNAAN MEDIA REALIA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - algiranto, algiranto; Yampap, Umar; Bay, Rudolfus Ruma (Universitas Muhammadiyah Mataram, 2021)
The research aims to improve science learning outcomes by using realia media for fourth-grade students of SD Negeri 2 Merauke. Classroom Action Research in cycle I and cycle II. The results of cycle I 2.87 and cycle II 3.53 are very good, student activities in cycle I 2.40 and cycle II 3.40 are good categories and learning outcomes. The first cycle is 64.9 good category and the second cycle is 71.83 good category. Cycle I 53.33 and cycle II 100% very good category. Based on these results, that improves student learning outcomes in heat transfer material.